Bamboozled - Legge, David, 1963- (New York : Scholastic, 1994)
During her weekly visit with her grandfather, a young girl feels that there is something out of the ordinary but cannot figure out what it is.
School Library Journal starred
Child Study Children's Book Committee
Publisher's Weekly
1.6
K-3
Keywords: Grandfathers -- Fiction; Family life -- Fiction; Grandfathers -- Fiction; Family life -- Fiction